Mising Grammar - Prasad, Bal Ram (Central Institute of Indian Languages Mysore, 1991)
This book is a language learning resource with detailed description of the grammatical function of Mishing language.
Keywords: Mishing; Miri; Grammar; Bharatavani; Knowledge Through Indian Languages; Grammar; Mishing